The Efficacy and Safety of Bimekizumab for Plaque Psoriasis: An Expert Consensus Panel - Joshua Burshtein; Milaan Shah; Danny Zakria; Benjamin Lockshin; Jeff Crowley; Joseph F. Merola; Ken Gordon; Mona Shahriari; Neil J. Korman; Raj Chovatiya; Robert Kalb; Mark Lebwohl (Adis, Springer Healthcare, 2024)
Abstract Introduction Psoriasis is a chronic inflammatory condition affecting the skin, joints, and several other organ systems with significant disease burden. Bimekizumab is the first monoclonal antibody targeting both interleukin (IL)-17A and interleukin-17F and has demonstrated efficacy for treating moderate to severe psoriasis. Limited guidelines exist for incorporating this drug into clinical practice. The purpose of this study was for a panel of experts in psoriasis management to synthesize current literature and provide consensus statements with guidance on use of bimekizumab. Methods A comprehensive literature search of PubMed, Scopus, and Google Scholar was completed for English-language original research articles on the use of bimekizumab for moderate to severe psoriasis and psoriatic arthritis. A panel of nine dermatologists with significant expertise in treatment of psoriasis gathered to review the articles and create consensus statements on this new medication. A modified Delphi process was used to approve each statement and a strength of recommendation was assigned using Strength of Recommendation Taxonomy criteria. Results The literature search produced 102 articles that met criteria. A thorough screening of the studies for relevance to the research question resulted in 19 articles. These were distributed to all panelists for review prior to a roundtable discussion. The panel unanimously voted to adopt 14 consensus statements and recommendations, 12 of which were given a strength of "A", one of which was given a strength of "B", and one of which was given a strength of "C". Conclusion Bimekizumab results in rapid and long-lasting clinical improvement for patients with moderate to severe plaque psoriasis and psoriatic arthritis. It has demonstrated superior efficacy when compared to several other biologics. The safety profile is consistent with other biologics, except for an increased incidence of oropharyngeal candidiasis.